Pengaruh Informasi Kadar Gula Darah Terkini dan Probabilitas Terjangkitnya Diabetes Mellitus terhadap Belief Updating dan Willingness to Pay Premi Asuransi Kesehatan - Restiatun, Restiatun (Fakultas Ekonomi dan Bisnis, UNTAN, 2015)
This research evaluates effect of the current information about blood glucose level based onmedical test to the value of the premium willingness to pay (WTP) and ownership of healthinsurance. The data collecting methodology in this study used laboratory experiments.Participants involved in this research is limited only to the individual that has been aged a minimum of thirty-five years and have a permanent income. The sample selection was based onthe fact that the individuals in that age have increasing tencendy in the prevalence of the risk contracting acute diseases, such diabetes mellitus. While the terms on permanent-income basedon the consideration that only income individuals who can afford to buy health insurance.Theresults of this study show that blood glucose current information significantly influencesubjective belief of health status which in turn affects the value of WTP and decisions of individuals in health insurancepossession. Other variables that significantly affect the individualhealth risk perceived are the number of sick days in a month. Other significant variable is income. While the ownership of health insurance is significantly only influenced by subjectivehealth status, after receiving the objective information based on blood glucose level medicalreport.